SHORT TERM EFFECT OF OSMOLYTE CONCENTRATION AND TEMPERATURE ON SURVIVABILITY OF FREE LIVING NEMATODE Acrobelus SPECIES - KOUSER, NAZIA; NISA, RAWHAT UN; KHAN, SALMAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The aim of this work was to assess the influence of different osmolyte concentrations on the viability and dormancy of free living Acrobelus nematode. A high-temperature (50°C) assay was done to check dormancy and viability. An extreme decrease in viability was noted when juveniles were exposed to high-temperature assay whereas non-desiccated juveniles died within short exposure to high temperature. Using the high-temperature assay, the mortality of desiccated nematodes was slow representing an improved capability to tolerate high-temperature conditions. At high osmolyte concentration (60%) maximum dormancy was observed. Variable recovery periods were noted when nematodes were exposed to two different temperatures. Low glycerol concentration at low temperature results in less recovery time.